Um século de tradição: a banda de música do Colégio Salesiano de Santa Rosa (1888-1988) - Higino, Elizete (2006)
Music at Salesian schools has always had an outstanding place, since according to Saint John Bosco’s pedagogy it is an important educational factor due to its great influence on the spirit of the young. For Don Bosco, 'a school with no music is a body without a soul,' a statement that stresses the pedagogic value of music. Still according to Don Bosco, joy is education’s basic element, and music expresses this state of the soul. This dissertation intends to show the importance of the Santa Rosa Salesian School Marching Band (Niterói, Brazil), in its career of over 100 years of uninterrupted activity, and retrieve a memory that might be lost. The band has always led the civic celebrations, exciting the public with patriotic marches and anthems, imposing its beat and expressing with its music the community’s feelings. The reason for this research was that other studies about marching bands have concentrated on the learning of music, but not on its pedagogic value. Also, there was nothing written about the Santa Rosa Salesian School Marching Band. Therefore, using historic documentation and memories as support for reconstructing the story of this centennial band, this dissertation takes a new look on the theme.